Pengembangan Kamus Biologi Interaktif SMA Kelas X Pada Semester Ganjil - Renny Afrianti; Eko Wulandari; Eni Yulianti (Pendidikan Biologi STKIP YPM Bangko, 2020)
This research is motivated by the difficulties of students in interpreting Latin terms or scientific language in textbooks, the glossary in textbooks is not sufficiet to mees the needs of students in searching for scientific terms. Teachers have not developed a biology dictionary at SMA N 20 Merangin as teaching material. Thist studied aims to describe the process of developing an interactivet biology dictionary for SMA class X in the odd semester and to produce a valid and practical interactive biology dictionary. This types of research is a development research that uses 4-D which includes the stages of define, design, develop, and disseminate. The subjects of this study consisted of 7 validators consisting of 6 STKIP YPM Bangko lecturers and 1 biology teacher at SMA N 20 Merangin. The research instrument used a validation questionnaire and practicality, so the data were analyzed by descriptive analysis. Based on the results of this study, the resulting product is an interactive biology dictionary for tenth grade High School in ood semsters, the dictionary is declared valid by the validator as evidenced the result of the assessment obtained that the feasibility of content, language, presentation, graphics with an averages validity valuet of 95%. The dictionary has also been declared practical with an average gain of 3.51 so that the interactive biology dictionary has been declared valid and practical.